Classes of oppositional‐defiant behavior: concurrent and predictive validity. (26th March 2014) - Althoff, Robert R.; Kuny‐Slock, Ana V.; Verhulst, Frank C.; Hudziak, James J.; van der Ende, Jan
<x xml:space="preserve">Abstract</x> Background Oppositional defiant disorder (ODD) has components of both irritability and defiance. It remains unclear whether children with variation in these domains have different adult outcomes. This study examined the concurrent and predictive validity of classes of oppositional defiant behavior. Methods Latent class analysis was performed on the oppositional defiant problems scale of the Child Behavior Checklist in two samples, one in the US (the Achenbach Normative Sample, N = 2029) and one in the Netherlands (the Zuid‐Holland Study, N = 2076). A third sample of American children (The Vermont Family Study, N = 399) was examined to determine concurrent validity with DSM diagnoses. Predictive validity over 14 years was assessed using the Zuid‐Holland Study. Results Four classes of oppositional defiant problems were consistent in the two latent class analyses: No Symptoms, All Symptoms, Irritable, and Defiant. Individuals in the No Symptoms Class were rarely diagnosed concurrently with ODD or any future disorder. Individuals in the All Symptoms Class had an increased frequency of concurrent childhood diagnosis of ODD and of violence in adulthood. Subjects in the Irritable Class had low concurrent diagnosis of ODD, but increased odds of adult mood disorders. Individuals in the Defiant Class had low concurrent diagnosis of ODD, but had increased odds of violence as adults. Conclusions Only children in the All Symptoms class were likely to have a concurrent diagnosis of ODD. Although not diagnosed with ODD, children in the Irritable Class were more likely to have adult mood disorders and children in the Defiant Class were more likely to engage in violent behavior.